Insurance for the future? Potential avian community resilience in cities across Europe - Morelli, Federico; Benedetti, Yanina; Ibáñez-Álamo, Juan Diego; Tryjanowski, Piotr; Jokimäki, Jukka; Kaisanlahti-Jokimäki, Marja-Liisa; Pérez-Contreras, Tomás; Sprau, Philipp; Suhonen, Jukka; Yosef, Reuven; Díaz, Mario; Møller, Anders Pape (Climatic Change, 2020)
Urbanization is affecting avian biodiversity across the planet and potentially increasing species vulnerability to climate change. Identifying the resilience of urban bird communities to climate change is critical for making conservation decisions. This study explores the pattern in bird communities across nine European cities and examines the projected impact of climate change in order to detect communities facing a higher risk of functional change in the future. First, generalized linear mixed models were used to explore the potential resilience of urban bird communities in nine European cities and the effects of land cover, latitude, abundance of potential predators (dogs and cats), and bird species richness in each trophic guild. Bird community resilience was represented by an index of functional evenness, because it indicates relatively uniform functional space within the species assemblages. Second, bird community resilience in each city was compared with projected changes in temperature and precipitation for the year 2070 to explore potential future threats to conservation. The results showed that community resilience was not significantly associated with land use or abundance of predator. The number of granivorous and granivorous-insectivorous species increases the potential resilience of the community, while the numbers of insectivores, carnivores, and omnivores was negatively correlated with resilience. Of the nine cities, Madrid and Toledo (Spain) are projected to experience the largest change in temperature and precipitation, although their bird communities are characterized by relative high resilience. In contrast, Rovaniemi, at the Arctic Circle (Finland) is projected to experience the second highest increase in temperature among the focused cities, and their bird communities are characterized by low resilience. These findings indicate the importance of future research on the combined effect of functional diversity of species assemblages and climate change on urban biodiversity. F.M. and Y.B. ...